From quantum communication fundamentals to decoherence mitigation strategies: Addressing global quantum network challenges and projected applications - Muhammad Annas Khan; Salman Ghafoor; Syed Mohammad Hassan Zaidi; Haibat Khan; Arsalan Ahmad (Heliyon, 2024)
In the aftermath of unparalleled disruptive technologies, the quantum realm has become a fundamental field of research due to unrivaled computational power and super-secure communication. In addition to conventional networks, a new word in the quantum domain is quantum network. The quantum network uses quantum communication (QC) to send quantum information bits known as qubits, to predetermined destination nodes. It governs the new quantum mechanics notions like superposition, quantum entanglement, the no-cloning theorem, and quantum teleportation. Quantum communication, like classical communication, is prone to noise, which is known as quantum decoherence. Quantum decoherence is a significant barrier to the implementation of a global quantum network. It deteriorates the quantum information, causing it to lie in an undetermined state. Environmental factors that cause quantum entanglement loss are the key factors that cause qubits to lose their states. To mitigate the impact of quantum decoherence, quantum error correction codes (QECC) and entanglement distillation have proved their potential. They add extra qubits or maintain entanglements among quantum networks. This survey presents quantum mechanics principles, quantum decoherence, and techniques to mitigate the effect of quantum decoherence. At the end, we highlighted some challenges in the realization of the quantum network, along with some projected applications.